THE OBJECTIVE AND SIGNIFICANCE OF PRIVATIZATION OF OBJECTS WHICH ARE STATE DEATH IN OUR COUNTRY (American Journal of Interdisciplinary Research and Development, 2024)
The article examines the opinions of leading scientists around the world on the importance and importance of privatization of state-owned objects in our country. The main indicators of privatization are studied, the proceeds from the sale of state assets are analyzed, the number of privatized enterprises and objects is analyzed, the importance and importance of privatization of state-owned objects in Uzbekistan-based conclusions and proposals were developed, and recommendations for application in our country were made.